A Combined Mode-Matching Technique and Born Approximation Method to Model Well-Logging Sensors in Non-Axisymmetric Boreholes - Lisseth Saavedra; Guilherme S. Rosa; Jose R. Bergmann (IEEE Access, 2021)
This paper presents a study on pseudo-analytic techniques for modeling electromagnetic sensors used in geophysical well logging. Logging-while-drilling (LWD) tools are sensors typically used on the exploration of hydrocarbons reservoirs and are usually immersed in complex geophysical formations (inhomogeneous, dissipative, and anisotropic), resulting in a challenging problem for conventional computational electromagnetic techniques. The geophysical environment is typically treated as a radially and longitudinally stratified medium, conforming with the boundaries of a cylindrical borehole drilled in the earth. We analyzed this propagation problem by using a full-wave method based on the mode-matching technique for solving the cylindrical stratifications. This method was then supplemented by a perturbational solution on the grounds of the Born approximation for handling the non-symmetries the borehole and earth layers can present. Preliminary results show the ability of the techniques introduced in this paper to accurately modeling electromagnetic sensors more realistically when compared with other semi-analytic methods available in the literature.